1997
DOI: 10.1172/jci119476
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of murine embryonic growth by human immunodeficiency virus envelope protein and its prevention by vasoactive intestinal peptide and activity-dependent neurotrophic factor.

Abstract: Intrauterine growth retardation and neurodevelopmental handicaps are common among infants born to HIV-positive mothers and may be due to the actions of virions and/or maternally derived viral products. The viral envelope protein, gp120, is toxic to neurons, induces neuronal dystrophy, and retards behavioral development in neonatal rats. Vasoactive intestinal peptide, a neuropeptide regulator of early postimplantation embryonic growth, and the neuroprotective protein, activity-dependent neurotrophic factor, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Injections of the same antiserum into pregnant mice inhibit CNS development, manifested in a smaller CNS at birth and apparently life‐long neurological deficits (Hill et al, 1997). In addition, developmental inhibition caused by gp 120 was prevented by treatment with ADNF (Dibbern et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Injections of the same antiserum into pregnant mice inhibit CNS development, manifested in a smaller CNS at birth and apparently life‐long neurological deficits (Hill et al, 1997). In addition, developmental inhibition caused by gp 120 was prevented by treatment with ADNF (Dibbern et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that vasoactive intestinal peptide (VIP) regulates growth and development during the early postimplantation period of mouse embryogenesis characterized by neural tube closure and the initiation of neuronogenesis. Treatment of embryonic day 9 (E9) whole cultured mouse embryos with a dose range of VIP showed a concentration dependent and dramatic increase in growth and development over a 4 h period (Gressens et al, 1993; Dibbern et al, 1997; Hill et al, 1999; Glazner et al, 1999; Servoss et al, 2001). Treatment with the same concentration range of the related peptide, pituitary adenylate cyclase polypeptide (PACAP) had no effect at low concentrations and an inhibitory effect on growth at higher concentrations (Hill et al, 1999), illustrating the different roles of these peptides during development.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with this, Brenneman et al [481] found that VIP treatment could result in the release of MIP-1α, RANTES, and chemokines to mediate the blockage of gp120 with microglial chemokine receptors. On top of this, VIP cotreatment could prevent the gp120-induced growth inhibition in mouse embryos, indicating a potential therapeutic strategy in using VIP to forestall the growth retardation as well as behavioral development experienced by infants born to HIVpositive mothers [482]. Apart from exogenous VIP application, recent case reports have also supported the putative therapeutic use of anti-VIP antibodies in AIDS management.…”
Section: Human Immunodeficiency Virus (Hiv)-associated Dementiamentioning
confidence: 89%